1982
DOI: 10.1002/lary.1982.92.6.657
|View full text |Cite
|
Sign up to set email alerts
|

Changing Face of Treatment of Peritonsillar Abscess

Abstract: Changing trends in the treatment of peritonsillar abscess are demonstrated by this retrospective study of 74 patients treated from 1975 through 1980 by a standardized regimen. This included needle aspiration at three points, intravenous antibiotics, hydration, and pharyngeal douches. The patients ' ages ranged from 11 to 73 years. There were 45 males and 29 females. Needle aspiration was positive in 52 patients (70%) and repeat aspiration was necessary in 10% of patients. Tonsillectomy was performed in 42 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…The incidence of recurrences of peritonsillar abscesses has been reported in the literature to vary between 0% following needle aspiration 10 and 22% following incision 17 . Harris, 18 who observed 36 patients who had been treated for peritonsillar abscess through tonsil‐conserving therapies, for a median time of 17 years, concluded from his results that abscess tonsillectomy in uncomplicated peritonsillar abscesses beyond the age of 40 years is not necessary if there has been no history of recurrent tonsillitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of recurrences of peritonsillar abscesses has been reported in the literature to vary between 0% following needle aspiration 10 and 22% following incision 17 . Harris, 18 who observed 36 patients who had been treated for peritonsillar abscess through tonsil‐conserving therapies, for a median time of 17 years, concluded from his results that abscess tonsillectomy in uncomplicated peritonsillar abscesses beyond the age of 40 years is not necessary if there has been no history of recurrent tonsillitis.…”
Section: Discussionmentioning
confidence: 99%
“…The mentioned procedures allow a confirmation of the diagnosis combined with simultaneous therapy and only minimal trauma 19–21 . Patients seem to tolerate needle aspiration better than other procedures; 10,22 there also seems to be less danger of accidental trauma to neighbouring structures. Additionally, instant alleviation of the symptoms could be noticed in most patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The failure rate of the initial aspiration controlling the disease was 10% in both studies. After the initial failure, we went to conventional rec¬ ommendations, ie, incision and drain¬ age and abscess tonsillectomy, where¬ as, in the study by Schechter et al,7 repeated aspiration controlled the disOne of the rationalizations for abscess tonsillectomy has been that peritonsillar abscess is a strong indi¬ cation for tonsillectomy because of its high recurrence rate. These data do not indicate this with 0% to 22% recurrence rates reported in patients who have had a single episode of peritonsillar abscess.1·7·8 Abscess ton¬ sillectomy is the most expensive ini¬ tial way of treating this disease as it requires both an operation and a hos¬ pital stay.…”
Section: Resultsmentioning
confidence: 99%
“…Several literatures are found comparing both management procedures showing almost same result. Studies have reported no significance differences between and incision regarding different outcomes like length of stay, resumption of normal diet, recurrence rate, [2][3][4] while few studies have reported in favour of aspiration. [5][6][7] However, Mansour et al has concluded incision has good result.…”
Section: Introductionmentioning
confidence: 98%